Comment: Racism and Custody Deaths in the U.K.: The Zahid Mubarek Inquiry - Moss, Nick (Social justice, 2006)
Part of a special issue on deaths in custody and detention. In 2004, a public inquiry began into the March 21, 2000, death of Zahid Mubarek following an unprovoked attack by Robert Stewart, his cellmate at Young Offenders Institution (YOI) Feltham, London. Central to the inquiry's concerns was racism, not only because Zahid died in a racially motivated attack but because Stewart was well known within the YOI as a violent racist. The inquiry sought to ascertain whether explicit or unwitting institutionalized racism had a part in the decision to pair Zahid with Stewart. The inquiry yields some insight into the brutalizing conditions at prisons and their fatal consequences.